Analisis Bibliometrik dengan VOSViewer pada Tren Penelitian Industri Hospitality : Studi Kasus Bidang Pemasaran Hotel - Wisnawa, I Made Bayu (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2024)
This study aimed to identify and analyze trends in hotel marketing research, examine co-authorship dynamics, and explore keyword co-occurrence through bibliometric analysis using VOSviewer from 2003 to 2023. The method involved a multi-stage approach employing Publish or Perish, Google Scholar, Excel, and VOSviewer for data extraction and trend analysis. Results indicated a significant growth in publications, highlighting customer expectations, service quality, and innovation as focal research topics. The study revealed a peak in publications before a slight downturn, possibly due to market dynamics or global events such as the pandemic. Limitations include the reliance on available databases, possibly omitting relevant literature, and not reflecting research quality. Future research should expand databases for a more comprehensive view, focus on the impact of research on industry practices and policies, and delve deeper into the relationship between technological innovations and marketing success.